BEHAVIORAL FINANCE DAN PENGARUHNYATERHADAP PENGAMBILAN KEPUTUSAN HUTANG (Studi Pada Usaha Kecil Dan Menengah (UKM) di Pulau Lombok ) - Siti Aisyah Hidayati; Sri Wahyulina; Embun Suryani (Master of Management, Mataram University, 2018)
This research aims to analyze: 1) The effect of overconfidence against debt decision-making on SME’s, 2) The Effect of the illusion of control against debt decision-making on SME’s, 3) The effect of availability against debt decision-making on SME’s.This research is a research-based approach to quantitative, with this type of research is explanatory research. The population of the research was all SME’s that are located on the island of Lombok. The technique of sampling done with Non probability sampling, i.e. using judgement sampling i.e. selecting SME’s engaged in pottery industry and already exports. Of the population, there are 35 (thirty five) SME’s which can be taken as a sample. The respondents in this study was a financial manager at the same time as the owner of each such SME’s. Data collection techniques used in this research is to use the question form. To achieve the research objectives and hypothesis testing, then the data acquired will be processed according to your needs by using statistical tools GSCA (Generalized Structured Component Analysis).The results showed: 1) Overconfidence has no significant effect on decision-making on debt undertaken by owner Managers, 2) Illusion of Control has significant effect on decision-making on debt undertaken by the SME owner managers, 3) Avaibility has no significant effect on decision-making on debt undertaken by the SME owner managers. This shows the SME’s managers in the selection of a rational debt as a source of funding. The rational attitude effected by the characteristics of respondents who was the Manager of the SME’s owner, i.e., the age of majority SME’s managers are still productive ranged from 37 to 54 years of age, mostly female, with a level of education mostly high school and college graduates, as well as long time effort over 10 years. Keywords: overconfidence, illusion of control, avaibility, decision making of debt